Vibrio and heterotrophic marine bacteria composition and abundance in nutrient-enriched Kappaphycus striatus - Tahiluddin, Albaris B.; Nuñal, Sharon N.; Luhan, Maria Rovilla J.; Santander de Leon, Sheila Mae S. (2021)
Inorganic nutrient application in Kappaphycus seaweed farming has been a practice in the southern Philippines for the past years. To investigate the inorganic nutrient's influence on the number and assemblage of Vibrio and heterotrophic marine bacteria and on the presence of ice-ice disease-inducing bacteria in Kappaphycus striatus, a field experiment was conducted using ammonium phosphate (16-20-0) fertilizer at high concentration (HC, 8.82 g L-1), low concentration (LC, 0.01 g L-1) and control (C, 0.00 g L -1). - Title page.
Includes bibliographical references.
Keywords: Heterotrophic bacteria -- Philippines -- Mindanao; Vibrio -- Philippines -- Mindanao; Marine algae -- Philippines -- Mindanao